INTERACTIVITY AND HOW TO USE IT FOR CREATING DIDACTIC INSTRUMENTS THAT USE POSSIBILITIES OF I-BOARDS - MARTINKOVA, Anna (Trends in education, 2009)
Interactive ICT are didactic instruments that enable to achieve defined aims in education in all school stages with the emphasis on active and creative learning not only passive information taking. Interactive boards represent one of innovation possibilities and with usage of interactive boards it is possible to create dynamic (high-response) instruments in Smart Notebook software application which lead learners to own thinking and creativity (examples from Technical education). Smart board videos offer another way of using for self study activities or individual learning (examples from Programming). Lessons of interactive teaching with the use Media Site technologies contribute to development of competences to work with these innovative instruments.
Keywords: Interactive ICT - Smart Board; video-conferences; Smart Bridgit; Smart Notebook; teaching (didactic) instruments; competences; video-recording; video teaching with Media Site technology.